Analisis Data Time Series Untuk Prediksi Harga Komoditas Pangan Menggunakan Autoregressive Integrated Moving Average - Sihombing, Ester Ivo; Suhendra, Christian Dwi; Marini, Lion Ferdinand (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
Onions and chilies are two of the many food commodities frequently used by Indonesian people in their daily lives. The high demand in the market leads to price instability, causing prices to fluctuate or remain unstable. This can result in farmers suffering losses when selling their agricultural products. Therefore, forecasting is conducted to predict future prices of onions and chilies. This can provide information on the estimated prices that farmers will set for sale to traders, which is expected to address market price instability. This research aims to obtain the best model from the Autoregressive Integrated Moving Average (ARIMA) for forecasting the prices of onions and chilies in Manokwari Regency in 2024. The data for this study is sourced from the SP2KP (Market and Basic Needs Monitoring System) website, consisting of price data for red onions, garlic, and bird's eye chilies from January 2016 to December 2023. The best ARIMA models based on the smallest AIC values are ARIMA (2,0,0) with an AIC of 1341.784, ARIMA (3,0,0) with an AIC of 1278.688, and ARIMA (1,0,0) with an AIC of 1466.834 for red onions, garlic, and bird's eye chilies respectively, with RMSE values of 7447.06, 3501.71, and 13787.59 respectively. From these models, the predicted prices of the three commodities in 2024 from January to December are as follows: red onions around Rp 50,000/kg, garlic around Rp 40,000/kg, and bird's eye chilies between Rp 50,000 and Rp 70,000/kg